Facile Fabrication of BiOI/BiOCl Immobilized Films With Improved Visible Light Photocatalytic Performance - Zhong, Yingxian; Liu, Yuehua; Wu, Shuang; Zhu, Yi; Chen, Hongbin; Yu, Xiang; Zhang, Yuanming (Frontiers in Chemistry, 2018)
HIGHLIGHTS A facial method was used to fabricate BiOI/BiOCl film at room temperature. 30% BiOI/BiOCl showed an excellent photocatalytic activity and stability. Improvement of photocatalytic activity was owed to expanded visible light absorption and high separation efficiency of charge. Photocatalysis has been considered to be one of the most promising ways to photodegrade organic pollutants. Herein, a series of BiOI/BiOCl films coating on FTO were fabricated through a simple method at room temperature. The photocatalytic efficiency of 30%BiOI/BiOCl could reach more than 99% aiming to degrading RhB and MB after 90 and 120 min, respectively. Compared with BiOCl, 30%BiOI/BiOCl showed 12 times higher efficiency when degrading RhB. In comparison with BiOI, 30%BiOI/BiOCl showed 5 and 6 times higher efficiency when degrading RhB and MB, respectively. These obvious enhancements were attributed to expanded visible light absorption and high separation performance of photoinduced charge. Moreover, the photocatalytic activity of 30%BiOI/BiOCl had no obvious decrease after five recycles, suggesting that it was a promising photocatalyst for the removal of MB and RhB pollutants. Finally, the possible growth process for the BiOI/BiOCl thin films and photocatalysis mechanism were investigated in details. This work would provide insight to the reasonable construction of BiOX heterojunction and the photocatalytic mechanism in degrading organic pollutants.